Male jurors, male awards? Research on the relationship between juries and award-winners at film festivals from a gender perspective - Jurado-Martin, Montserrat (MedieKultur: Journal of media and communication research, 2024)
Film festivals are an added value to the film industry. The research of these events is growing, although it is limited in terms of jury committees, and less so in terms of gender bias. The initial assumption is that if juries are mainly made up of men, awards will be given mainly to men. In the context of Spain, this process is related to the fact that the most prominent jobs in the film process are still held by men (Arranz et al, 2007). This paper discusses the composition of the juries and the awards given at animation film festivals in Spain in 2022 as an approach to the study of juries from a gender perspective. The first results show that awards are predominantly made up of men (65%), despite the fact that, the juries are made up mostly of women (60.42%). This shows an imbalance: although there is more female presence on the juries, the majority of the awards continue to be given to men.